2003
DOI: 10.1080/0965254032000102939
|View full text |Cite
|
Sign up to set email alerts
|

Relating marketing expertise on the top management team and strategic market aggressiveness to financial performance and shareholder value

Abstract: Understanding the impact of marketing on firm performance has received considerable attention in recent years. To further explore this issue, the authors explore top management team composition and strategic market aggressiveness in a conceptual model that integrates research in marketing and strategic management. The model is tested using 20 quarters of objective data on 173 firms across 47 industries. Path analysis indicates that inclusion of marketing expertise on the top management team and aggressive depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 108 publications
(282 reference statements)
0
18
0
1
Order By: Relevance
“…Research has shown the consequences of firms' aggressive investment using their expenditures in R&D and deployment of financing. While contingent on the firm's environment, several studies have shown better financial performance for those firms that undertake greater commitment in the investment and exploitation of resources to achieve a competitive advantage (Feeser & Willard, 1990;Fombrun & Ginsberg, 1990;Grinyer, McKiernan, & Yasai-Ardekani, 1988;Weinzimmer, Bond III, Houston, & Nystrom, 2003). 9 Our study differs from this research in that we consider individuals', rather than firms', investment choices.…”
Section: Implications For Theory and Practicementioning
confidence: 97%
“…Research has shown the consequences of firms' aggressive investment using their expenditures in R&D and deployment of financing. While contingent on the firm's environment, several studies have shown better financial performance for those firms that undertake greater commitment in the investment and exploitation of resources to achieve a competitive advantage (Feeser & Willard, 1990;Fombrun & Ginsberg, 1990;Grinyer, McKiernan, & Yasai-Ardekani, 1988;Weinzimmer, Bond III, Houston, & Nystrom, 2003). 9 Our study differs from this research in that we consider individuals', rather than firms', investment choices.…”
Section: Implications For Theory and Practicementioning
confidence: 97%
“…encouraging rapid learning and technical advances (Weinzimmer, Bond, Houston, & Nystrom, 2003). Hence:…”
Section: Journal Of Strategic Marketing 271mentioning
confidence: 99%
“…Despite evidence of the marketer"s apparent value to the organisation (e.g. Weinzimmer, et al, 2003) what chance, then, a place at the heart of the organization -with an opportunity to seize and influence the strategic imperative?…”
Section: Notion Of Marketing As Grandmentioning
confidence: 99%